Rational Emotive Group Counseling Behavior Therapy on Self-Esteem and Addiction Game Online - Riduwan, Muhd.; Sunawan, Sunawan; Sugiyo, Sugiyo (Jurnal Bimbingan Konseling, 2020)
The purpose of this study was to determine the effectiveness of group counseling with rational emotive behavior therapy approach to increase self-esteem and reducing online gaming addiction. This study design using non-equivalent control group pre-test – post-test design. Purposive sampling technique is used to select 14 students as research subjects. Each 7 students are placed in the experimental group and a control group so that the two groups had the same initial conditions. MANOVA test results showed that group counseling rational emotive behavior therapy approach is effective in improving self-esteem (F3.10= 24.237; p < 0.01) and reducing online gaming addiction (F3.10=29.756; p < 0.01). Furthermore, the Wilcoxon test results showed that the experimental group an increase in self-esteem (z = -2.371; p < 0.05), and a decrease in online gaming addiction (z = -2.375; P <0.05) were significant. While the control group an increase in self-esteem (z =-.175; p > 0.05) and a decrease in online gaming addiction (z = -1.342; p > 0.05) did not occur significantly. The findings of this study confirms that counseling group with rational emotive behavior therapy approach is effective in improving self-esteem and lower addicted to online games.